The devil's tomb - Connery, Jason, 1963-; Gooding, Cuba, Jr., 1968-; Perlman, Ron, 1950-; Winstone, Ray, 1957- (Culver City, Calif. : Sony Pictures Home Entertainment, 2009)
On a mission to rescue a scienctist in an underground lab, a special ops team discovers an ancient evil.
Widescreen.
Originally released as a motion picture direct-to-video in 2009.
Features: audio commentary, outtakes, alternate scenes, Beneath the desert : behind the scenes of "The Devil's tomb."
Cuba Gooding Jr., Ron Perlman, Ray Winstone, Henry Rollins, Valerie Cruz, Frankie G, Stephanie Jacobsen, Taryn Manning.
MPAA rating: R.
DVD, Dolby digital 5.1 surround.
Keywords: Excavations (Archaeology) -- Drama; Supernatural -- Drama; Special forces (Military science) -- Drama; Feature films; Horror films; Science fiction films